Construction, characterization, and application of immature peach powder-stabilized Pickering emulsion gel - Wu, Limin; Liang, Yalong; Lu, Ninghai; Liu, Benguo (Frontiers in Nutrition, 2025)
This study utilized immature peach powder (IPP) as a stabilizer to construct a food-grade Pickering emulsion gel system. The effects of IPP concentration (w) and oil phase volume fraction (ϕ) on its structure and properties were investigated, with subsequent application as a butter substitute in cake production. Results indicated that IPP exhibited diverse morphologies and broad size distribution (5–96 μm), with a three-phase contact angle of 75.62° ± 1.27°, demonstrating potential for stabilizing Pickering emulsions. The O/W-type Pickering emulsion gels with ϕ ≥ 60% were achieved at w ≥ 3%. Droplet size was negatively correlated with w and positively correlated with ϕ, while gel strength showed positive correlations with both parameters. All emulsion gels displayed solid-like viscoelastic behavior and pseudoplasticity in rheological tests. The gel prepared at w = 4% and ϕ = 60% successfully partially replaced butter in cakes while maintaining normal texture and structure. These findings can promote the application of IPP in foods.